Modeling the operation processes in food manufacturing by using simulation technique - Kim Chen, Sick (2014)
This study discusses about modeling the operation processes in food manufacturing by using simulation technique. The scope of this study is to focus on the production processes of chili sauce’s company. The time frame covered is one year which is in year 2014. This study is conducted by using ARENA simulation software to simulate the modeled of chili sauce production processes in the simulation software. It is a quantitative study which the performance of the processes is measured by the average cycle time for the Whole system of chili sauce processes. The results of the simulation model of the chili sauce processes has determined the bottleneck in the process and measured output of the process. The improvement has been made by using “What-if Analysis” and scenario planning approach.